2010
DOI: 10.1007/s00066-010-8001-2
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Radiotherapy as Accelerated Partial Breast Irradiation for Early Breast Cancer

Abstract: Intraoperative radiotherapy (IORT) was originally introduced in breast cancer treatment as an "anticipated boost" during the procedure of breast conserving surgery (BCS). In addition to whole breast irradiation (WBI), it has yielded excellent long-term results [31, 38]. Under the assumption that the majority of in-breast tumor recurrences (IBTR) occur in the originally affected site, accelerated partial breast irradiation (APBI) as the sole treatment modality was initiated in several studies and with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 36 publications
0
28
0
1
Order By: Relevance
“…Mortality without recurrence was slightly higher in the irradiated group (1.09, 2p 0.14) but the excess was not significant and identiEditorial Tab. 1 The 10-year recurrence a rate and mortality [6] All patients (n =1 0,801) pN0 (n = 7,287) pN+ (n = Several new treatment modalities are currently being discussed like partial breast irradiation [10], or omitting axillary dissection (without irradiating the axilla instead!) in patients with a positive sentinel node and a clinically negative axilla [9].…”
Section: Commentmentioning
confidence: 99%
“…Mortality without recurrence was slightly higher in the irradiated group (1.09, 2p 0.14) but the excess was not significant and identiEditorial Tab. 1 The 10-year recurrence a rate and mortality [6] All patients (n =1 0,801) pN0 (n = 7,287) pN+ (n = Several new treatment modalities are currently being discussed like partial breast irradiation [10], or omitting axillary dissection (without irradiating the axilla instead!) in patients with a positive sentinel node and a clinically negative axilla [9].…”
Section: Commentmentioning
confidence: 99%
“…It is mainly used as an adjuvant to surgery or as a preliminary boost to be followed later by fractionated conventional external whole‐breast radiotherapy (WBRT) (1) . The objective is to achieve a higher dose in the target volume, while dose‐limiting structures are surgically displaced (2) …”
Section: Introductionmentioning
confidence: 99%
“…Bilateral, multifocal or multicentric breast cancer patients with clinical positive lymph nodes or patients with extensive ductal carcinoma in situ are not candidate for IORT. Contraindications for standard RT such as connective tissue diseases, and pregnancy (although in the EIO preliminary study potential fetal radiation exposure was found to be negligible) are also contraindications for IORT (39,40).…”
Section: Which Breast Cancer Patients Are Not Suitable For Iort?mentioning
confidence: 99%
“…An aluminum disk is placed on the pectoral muscle to protect thoracic tissues from irradiation, the skin is moved away from the applicator by as much retraction as possible. The total administered dose of 21 Gy is considered biologically equal to 60 Gy radiation applied for 5 weeks (13)(14)(15). Axxent Electronic Brachytherapy (Intracavitary systems) System (Xoft Inc., Fremont, CA) is a balloon-based brachytherapy system, and uses a 50 kilovoltage electronic radiation source.…”
Section: Iort Techniquesmentioning
confidence: 99%